2021
DOI: 10.1101/2021.01.22.427870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of auditory responses by visual inputs in the mouse auditory cortex

Abstract: So far, our understanding on the role of the auditory cortex (ACX) in processing visual information has been limited to infragranular layers of the ACX, which have been shown to respond to visual stimulation. Here, we investigate the neurons in supragranular layers of the mouse ACX using 2-photon calcium imaging. Contrary to previous reports, here we show that more than 20% of responding neurons in layer2/3 of the ACX respond to full-field visual stimulation. These responses occur by both excitation and hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…While doing this, we recorded activity in L2/3 neurons of ACx using two-photon calcium imaging. Using this approach, we first confirmed that a substantial subset of L2/3 neurons in ACx responds to either auditory, visual (Sharma et al, 2021), or motor-related inputs (Henschke et al, 2021; Morandell et al, 2023; Vivaldo et al, 2023). While we found that L2/3 neurons in ACx responded to audiomotor mismatches in a way that closely resembles visuomotor mismatch responses found in V1 (Keller et al, 2012), we found no evidence of responses to visuomotor mismatch in ACx.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…While doing this, we recorded activity in L2/3 neurons of ACx using two-photon calcium imaging. Using this approach, we first confirmed that a substantial subset of L2/3 neurons in ACx responds to either auditory, visual (Sharma et al, 2021), or motor-related inputs (Henschke et al, 2021; Morandell et al, 2023; Vivaldo et al, 2023). While we found that L2/3 neurons in ACx responded to audiomotor mismatches in a way that closely resembles visuomotor mismatch responses found in V1 (Keller et al, 2012), we found no evidence of responses to visuomotor mismatch in ACx.…”
Section: Introductionmentioning
confidence: 75%
“…Consistent with previous reports, we found that auditory, visual, and motor-related signals are intermixed in the population of L2/3 neurons in ACx. Responses to both motor-related (McGinley et al, 2015; Schneider et al, 2014; Vivaldo et al, 2023; Yavorska and Wehr, 2021; Zhou et al, 2014) and visual signals (Bigelow et al, 2022; Morrill and Hasenstaub, 2018; Sharma et al, 2021) have been reported across layers in ACx, with the strongest running modulation effect found in L2/3 (Schneider et al, 2014). Also, consistent with previous reports, we found that a subset of L2/3 neurons in ACx respond to audiomotor prediction errors (Audette et al, 2022; Liu and Kanold, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We first performed widefield Ca 2+ imaging 55,56 (see Methods) to identify location of A1 with UF 57,58 and other auditory areas 59 (Fig. 5A).…”
Section: Somatostatin (Som) Positive Interneurons and Thy-1 Excitatory Neurons Behave Differentially During Observed Experience Dependentmentioning
confidence: 99%